Perancangan Sistem Informasi Radio Online Universitas Nasional Berbasis Web - Ibnu Bukhari; Mohammad Iwan Wahyuddin; Novi Dian Nathasia (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Radio in a college has now developed sufficiently. Radio Unas is a radio broadcast owned by the National University that is managed by the Unas TV and Radio Laboratory. Present online radio or website based radio streaming. Radio streaming is a technology that sends audio files simultaneously to many users. The purpose of this research is to build and develop a National University online radio using Icecast as a freeware and winamp streaming radio as software used for radio broadcast media. The design of this information system through several discussions is a needs analysis, system design, testing and implementation. With streaming radio at the National University, the public and students of the National University do not miss the latest information about the National University and become a means of entertainment for National University students and the public as long as they are connected to the internet. From the trial results of the National University's online radio site, the streaming radio system can help the public and students of the National University to provide streaming radio content, listen to music and view activities from the National University Radio through the website